DIURETIC TEST OF HERB SELEDRI WATER BOILED (Apium graveolens L.) - Lamondo, Djuna (Sainstek, 2007)
This research was conducted at Biology Laboratorium FMIPA Gorontalo State University. The time range for this research was 2 month (Mey, 13 rd to June, 13 rd 2006). The subject was hamster siria amount 15 of age 4 months. The method of this research was experimental that consist of 3 treatments and 5 repeats. Treatment A: hamster siria was added herba seledri water boiled by 0.06 gr/30 gr BB dosis. The dosis was found by pre research. Treatment B: hamster siria was added furosemida suspension into NACMC 1% by 0.0006 gr/30 gr BB as positive control. Treatment C: hamster siria was added aquades 2.5 ml/30 gr BB as negative control. Variables that was searched were dependent variable of herba seledri water boiled and independent variable was hamster siria urine volume. For analysing data researcher used Kruskal-willis test. Result of this research saw that total volume of hamster urine added by herba seledri water boiled was high, namely 17.78 ml and volume of hamster urine added by treatment of furosemida suspension 9.3 ml and volume of hamster urine added by water flame was 4.3. Average of hamster urine volume added by herba seledri water boiled was higher 4 ml than average hamster urine volume added by treatment of furosemida suspension 1.8 ml, and average of hamster urine added by water flame was 0.8 ml. Based on statistic test saw that value H = 38.18 higher than value X o,os (2) = 5.991, so Ho wasnt accepted. Finally, it can be concluded that herba seledri water boiled added to hamster siria has diuretic effect.